Tell no one : a novel - Coben, Harlan, 1962- (New York, N.Y. : Delacorte Press, 2001)
Eight years ago David Beck was knocked unconscious and left for dead, and his wife Elizabeth was kidnapped and murdered. For the next eight years Dr. Beck re-lived the horror of what happened that day every day of his life. Then one afternoon, he receives an anonymous e-mail telling him to log on to a certain web site at a certain time, using a code that only he and his wife knew. The screen opens onto a web cam and it is Elizabeth's image he sees. Is it a practical joke? But as Beck tries to find out if Elizabeth is truly alive and what really happened the night she disappeared, the FBI are trying to pin Elizabeth's murder on him, and everyone he turns to seems to end up dead...
1 3 9 11 13 17 18 19 20 26 30 31 33 39
Keywords: Physicians -- Fiction; Mystery fiction